2008
DOI: 10.1111/j.1467-789x.2007.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of obesity‐related chronic diseases in Mainland China

Abstract: The objectives of the present study are: (i) to estimate annual direct medical costs of chronic diseases attributable to overweight and obesity among adults in China and (ii) to predict the medical costs if the epidemic continues developing. Using 2002 National Nutrition and Health Survey (n = 39,834), the prevalence of overweight [24 > or = body mass index (BMI) < 28] and obesity (BMI > or = 28), and population attributable risks (PARs) for hypertension, type 2 diabetes, coronary heart disease and stroke were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 16 publications
1
78
0
1
Order By: Relevance
“…Aging men and women who are overweight or obese had 6-17% higher lifetime healthcare expenditures than those of normal weight (Yang and Hall 2008). Further, a recent study estimated annual direct medical costs of chronic diseases attributable to overweight and obesity among adults in China to be $2.74 billion, accounting for 3.7% of national total medical costs (Zhao et al 2008). A Chinese case study also found that the indirect economic effects of obesity and obesity-related dietary and physical activity patterns accounted for 3.58% of that country's gross national product (GNP) in 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Aging men and women who are overweight or obese had 6-17% higher lifetime healthcare expenditures than those of normal weight (Yang and Hall 2008). Further, a recent study estimated annual direct medical costs of chronic diseases attributable to overweight and obesity among adults in China to be $2.74 billion, accounting for 3.7% of national total medical costs (Zhao et al 2008). A Chinese case study also found that the indirect economic effects of obesity and obesity-related dietary and physical activity patterns accounted for 3.58% of that country's gross national product (GNP) in 2000.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the mainland China expended nearly 21.1 billion Yuans (about $2.74 billion) in medical costs of overweight and obesity, counting nearly 25.5% of the total costs of medical care of chronic diseases and nearly 3.7% of national total medical costs [35]. The expenses of obesity alone in China in 2000 were about $50 billion and expected to rise to about %112 billion by 2025 [36].…”
Section: Economic Cost Of Obesitymentioning
confidence: 99%
“…Besides human suffering, loss to the Chinese economy from the consequences of diabetes, heart disease, and stroke between 2005 and 2015 will amount to $550 billion [6]. Thirty percent of Chinese adults are either overweight or obese [7], and estimates are that 92.4 million Chinese, nearly 10% of the adult population, suffer from type 2 diabetes, more than any other nation with future sharp increases expected [8][9][10][11].…”
Section: The Ncd Epidemic In Chinamentioning
confidence: 99%